The process of piling work with bore pile method / Muhamad Afiq Azfar Mat Zin - Mat Zin, Muhamad Afiq Azfar (Universiti Teknologi Mara, Perak, 2014)
Practical training is a training industry that brings students closer about the real nature of construction jobs. Students are allowed to undergo practical training in the government sector or the private sector and students are allowed to apply for a place was selected by self. During the 16 weeks of practical training at the project site in Jeli, I have identified several topics of study in accordance with the work done on the construction site and after discussion with my supervisor what title that suitable for final report. I chosen the title The process piling work with bore pile method. The real aim of the practical training is to provide an opportunity for students to practice the theory learned in the classroom and used for real work in industries. So students can acquire new knowledge and great experience during this Industrial Training while it helps the students to get jobs. In conclusion, this is absolutely compulsory industrial training conducted for all students because it is the best method to expose students to real working conditions on site.